Pendidikan Keluarga dalam Islam: Strategi dan Implementasinya dalam Kehidupan Modern - Achmad Hasan Alfarisi; Zainal (PT PUSTAKA CENDEKIA GROUP, 2024)
The marriage age contained in Law No. 16 of 2019 as an amendment to Law No. 1 of 1974 concerning Marriage has provided enormous benefits, where initially 16 years for women and 19 years for men has changed to 19 years for men. boy and 16 year old girl. This should be appreciated because the struggle to revise Law No. 1 of 1974 has been approved by the Constitutional Court. The age requirement set by the Constitutional Court is 19 years for men who are considered to have reached maturity in their attitudes, are capable of acting, and are responsible for their actions. Meanwhile, 19 year old women are considered mature and capable of running a household life. By using library research, there are three results of this research. First, Islamic law does not stipulate a minimum age for prospective brides and grooms who will carry out marriage. The foqoha' have different opinions in determining the age of maturity of a person in carrying out a marriage, but have the same goal, namely upholding the goals of Islamic law. Second, psychologists are of the opinion that the age of maturity (adolescence) is appropriate for carrying out marriage, namely someone aged 21 years and so on. Third, as a result of premature marriage, legal problems, biological problems, psychological problems, social problems and deviant sexual behavior problems will arise.